Analysis, development and implementation of adaptive algorithms for (flexible) traffic light regulations - V. N. Rutkovsky; D. V. Kapski (Системный анализ и прикладная информатика, 2023)
The article analyzes various adaptive control algorithms used in the intelligent system of the largest city – Minsk. An adaptive control algorithm has been developed depending on the dynamically changing load of a local intersection. On the example of one of the intersections, an example of the implementation of this algorithm is given. Recommendations are given for the further application of this algorithm on the street network.